solve this one

Asked by  | 18th Nov, 2008, 08:41: PM

Expert Answer:

p2x2+(p2-q2)x-q2=0

This equation is in a way already split into factors . The product : - p2q2 x2  is obtained by multiplying the two middle terms p2x and - q 2 x.

So just factorise as : p2x2 +p2x - q2x - q2=0

so , p2 x ( x +1) -  q2 (x+1) =0

i.e (p2x-q2) (x+1)=0

ie. x = q2/ p2  or x = -1

 

Answered by  | 19th Nov, 2008, 08:18: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.